Comparison of the grover, zmijewski, and springate methods in predicting financial distress (Case study of pharmaceutical companies listed on the IDX 2019-2021) (Lighthouse Publishing, 2023)
Financial distress is a condition of financial difficulties experienced by companies. The company's negative net income can mark this. If this condition continues, the worst possibility is that the company will go bankrupt. Several studies have developed methods to make it easier for companies to detect early if the company is in an unhealthy condition. This study aims to determine the differences between the Grover, Zmijewski, and Springate methods in predicting financial distress in pharmaceutical companies. The population used in this study was 11 pharmaceutical companies registered on the IDX for 2019-2021, with a sample selection using a purposive sampling technique. The independent variables in this study are the Grover, Zmijewski, and Springate methods, with the dependent variable being financial distress. The data analysis technique used in this study is a statistical analysis using variable calculations from each method, normality test, paired sample T-test, level of accuracy and type of error. The results showed that the method with the highest level of accuracy was Grover with 96.97%, then Zmijewski with 84.85% and Springate with 72.73%. The Paired Sample T-Test test shows that each method has a significant difference even though several methods use the same variables. For further research, more company samples and a more extended observation period can be used so that the results are wider.